(untitled) (Spectrum, 2023)
The horror genre as a whole is often overlooked in research and even less attention is paid to its various subgenres. One such subgenre is cosmic horror or Lovecraftian horror which focuses on the horror of all that is unknowable and incomprehensible. Dreams have been an integral part of folklore and are associated with the unknown. It is, thus, no surprise that they feature heavily in Lovecraft’s short stories, novellas, and poems. This article will utilise textual analysis and a psychoanalytic approach to explore the role that dreams play in the works of H.P. Lovecraft and, by extension, the genre of cosmic horror. A close reading of the short stories “Beyond the Wall of Sleep” (1919), “The Dreams in the Witch House” (1933), and the novella The Dream-Quest of Unknown Kadath (1943) show that dreams in Lovecraft’s works stem from the repressed memories and the collective unconscious of the human race and also act as a passage into other worlds and alternate dimensions of a vast, multidimensional cosmos. The findings show that Lovecraft uses these dreams as a device to explore themes and ideas like absurdism, nihilism, alienation and fragmentation which, together with his unique style, puts Lovecraft’s cosmic horror in the ranks of early twentieth-century texts that are considered quintessential modernist works. Spectrum, Volume 17, June 2022: 89-100